2019
DOI: 10.1108/tqm-02-2019-0048
|View full text |Cite
|
Sign up to set email alerts
|

Improving the 1040 process by applying lean principles: a case study

Abstract: Purpose The purpose of this paper is to investigate a subject accounting firm’s existing workflow processes for preparing individual tax returns with an emphasis on identifying predominant areas of waste. Design/methodology/approach Specific Quality and Lean tools were applied to qualitative data secured from on-site visits to the firm. Quantitative data analysis of productivity measures was performed to identify additional sources of muda (waste) as well as validate the findings from the qualitative analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
1
1
0
Order By: Relevance
“…Other authors have begun to find Muda in specific processes such as accounting and financial auditing (tax return process). However, typologies such as defects and delay continue to be presented, the same classification found in our research (Walters et al , 2019).…”
Section: Discussion/conclusion and Managerial Aspectssupporting
confidence: 82%
“…Other authors have begun to find Muda in specific processes such as accounting and financial auditing (tax return process). However, typologies such as defects and delay continue to be presented, the same classification found in our research (Walters et al , 2019).…”
Section: Discussion/conclusion and Managerial Aspectssupporting
confidence: 82%
“…In the educational sector, Doman indicates that with process innovation efforts, the graduate and graduate management processes can be improved [79]. Walters et al identified specific areas of internal production waste including defects and waiting, and in the process of our investigation, identified a significant shift in process efficiency due to resource allocation [80] focusing on 1040 financial norms. In fact, Ann Douglas et al similarly identified the 8 types of muda in Higher Education [81] and Suárez-Barraza et al also identified three new types of muda in the 21st century such as unnecessary emails, excess work meetings, and technological distractors [82]; processes in hospitals cannot be free of these three new types of muda either.…”
Section: Discussionmentioning
confidence: 80%